Sustainability bonds. An international event study - Mocanu, Mihaela; Constantin, Laura-Gabriela; Cernat-Gruici, Bogdan (Journal of Business Economics and Management, 2021)
Sustainability bonds enable capital-raising and investment for those projects that have both a positive impact on the environment and a positive social outcome. This study examines the stock market reaction to the announcement of sustainability bonds issuance. The present research is designed as follows: first, an event study that examines the market reaction and second, a highlight of drivers influencing this market reaction via a linear regression with cluster-robust standard errors. Overall, small and negative sample-wide reactions to sustainability bond issue announcements were found. Additionally, the study finds significant negative abnormal returns before the publication in June 2018 of The Sustainability Bond Guidelines by the International Capital Market Association. Specifically, the size of the bond issue, whether the bond is callable or not, the announcement of the issue as a single event in a day, the company’s Return on Assets, the firm’s social disclosure score, and the issuance of the bond prior or after June 2018 are statistically significant factors that influence the stock returns of issuers.